Dissolved Organic Matter in the Upwelling System off Peru: Imprints of Bacterial Activity and Water Mass Characteristics. Issue 6 (9th June 2021) - Maßmig, Marie; Engel, Anja
Abstract: Microbial degradation of dissolved organic matter (DOM) contributes to the formation and preservation of oxygen minimum zones (OMZs) in the ocean, but information on the spatial distribution and molecular composition of DOM in OMZ regions is scarce. We quantified molecular components of DOM that is, dissolved amino acids (DAA) and dissolved combined carbohydrates (DCCHO), in the upwelling region off Peru. We found the highest concentrations of DCCHO in fully oxygenated surface waters steeply declining at shallow depth. The highest DAA concentrations were observed close to the surface also, but attenuation of DAA concentration over depth was less pronounced. Compositional changes of DCCHO were strongest within more oxygenated waters. Compositional changes of DAA were also evident under suboxic conditions (<5 µmol O2 kg −1 ) and indicated bacterial peptide degradation. Moreover, specific free amino acids (alanine and threonine) were enhanced within suboxic waters, pointing to a potential production of dissolved organic nitrogen under suboxic conditions. Our results therewith suggest that deoxygenation supports a spatial decoupling of DCCHO and DAA production and degradation dynamics and give new insights to carbon and nitrogen cycling in the OMZ off Peru. Plain Language Summary: The molecular composition of dissolved organic matter (DOM) in seawater mainly depends on production and consumption processes by plankton organisms. The biological consumption of DOM reduces the amount of oxygen in seawater, but little is known about the composition of DOM in so‐called oxygen minimum zones (OMZs). We studied the distribution of DOM, specifically of dissolved sugars and amino acids in the OMZ off Peru. We observed that the reworking and degradation of sugars and amino acids differed between more and less oxygenated waters. We also found indications for the production of specific amino acids within the OMZ. Our study therewith suggests, that oxygen concentrations affect dissolved amino acid and sugar dynamics and may help to better understand carbon and nitrogen cycling within OMZs. Key Points: Decoupling of dissolved combined carbohydrates and dissolved amino acids dynamics, in the oxygen minimum zone off Peru Free amino acids indicate production of dissolved organic nitrogen within suboxic waters